Modified cellulose nanocrystal as well as preparation method and application thereof
By using modified cellulose nanocrystals in skin care products, the shortcomings of existing skin care products in dealing with the problem of high skin temperature are solved, and effective radiation refrigeration and cooling effect is achieved, which relieves skin heat stress and has good stability and moisturizing functions.
Patent Information
- Application Number
- CN202411824317.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
Existing skin care products have shortcomings in dealing with the discomfort caused by the high temperature environment, especially inability to effectively protect the thermal effects caused by the increase in skin temperature.
By adding modified cellulose nanocrystals to skin care products, the nanocrystals are modified by sodium alginate and calcium lactate, with high infrared emissivity and reflectivity in the sunlight band, which can effectively radiate heat on the skin surface and reduce skin temperature.
Modified cellulose nanocrystals can effectively reduce the temperature raised by the skin due to heat radiation in the external environment, provide a continuous cooling effect, alleviate the skin's heat stress response in a high-temperature environment, reduce skin problems caused by heat damage, and also have good stability and moisturizing functions.
Smart Images

Figure CN119632874A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cosmetics, and in particular to a modified cellulose nanocrystal and a preparation method and application thereof. Background Art
[0002] With global warming and people's increasing attention to skin health and comfort, the development of skin care products with innovative functions has become an important research direction in the cosmetics industry. In daily life, the skin is often exposed to various environmental factors, among which the impact of high temperature environment on the skin is particularly significant. Traditional skin care lotions mainly focus on moisturizing, whitening, anti-wrinkle and other functions, and they are obviously insufficient in dealing with the discomfort caused by high temperature on the skin. When the skin is in a high temperature environment, for example, long-term exposure to sunlight or in hot climate conditions, the skin surface temperature will increase. Excessive skin temperature may cause a series of skin problems, such as increased water loss, skin redness, fever, increased inflammatory response, and accelerated skin aging.
[0003] At present, there are limited solutions to the problem of high skin temperature on the market. Some sunscreen products mainly focus on blocking the damage of ultraviolet rays to the skin, but they are insufficient to protect against the increase in skin temperature caused by solar radiation and the resulting thermal effects. Radiative cooling, as an emerging passive cooling technology, has shown great application potential in the fields of architecture, textiles, etc. The application of radiative cooling technology in the field of skin care products can provide a new idea and method for solving the problem of heat stress of the skin in a high temperature environment. By adding functional ingredients with high emissivity to skin care emulsions, the skin surface can effectively radiate heat while absorbing heat, thereby reducing the skin surface temperature and alleviating the adverse effects of high temperature on the skin. However, at present, radiative cooling emulsions are mainly used in the field of energy conservation in room temperature buildings by adding nanoparticles such as titanium dioxide, silicon dioxide or aluminum dioxide. Oxide nanoparticles have potential hazards to human health, and their compatibility with the human body needs to be further improved. Safe and healthy radiative cooling cosmetics have not been reported in the literature. Therefore, the development of a skin care lotion based on radiation cooling technology has important practical significance and broad market prospects. It can fill the shortcomings of existing skin care products in dealing with high temperature problems of the skin and provide consumers with a more comprehensive and effective skin care product. Summary of the invention
[0004] In view of the shortcomings of skin care products in the prior art in dealing with the problem of high temperature on the skin, the present invention provides a modified cellulose nanocrystal and a preparation method and application thereof.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] In a first aspect, the present invention provides a modified cellulose nanocrystal, which is prepared by modifying cellulose nanocrystal with sodium alginate and calcium lactate.
[0007] There are many challenges in applying radiant cooling technology to the preparation of skin care emulsions. First, it is necessary to screen out functional materials that are suitable for adding to skin care products and have high emissivity and are safe and harmless to the skin. These materials must not only be able to exist stably in the emulsion system and not affect the basic properties of the emulsion, such as stability, fluidity, and spreadability, but also have good compatibility with other ingredients in the emulsion (such as moisturizers, emulsifiers, preservatives, etc.). Secondly, it is also necessary to consider the product's usage experience, such as texture, smell, color and other factors, so that it meets consumers' sensory requirements for skin care products.
[0008] Cellulose nanocrystals themselves have certain infrared emission characteristics. After being modified with sodium alginate and calcium lactate, their infrared emissivity in the atmospheric window band (8-13 μm) and reflectivity in the sunlight band are further improved. After being applied to the skin surface, skin care products or cosmetics containing the modified cellulose nanocrystals can more efficiently dissipate the heat absorbed by the skin in the form of radiation, thereby effectively reducing the temperature of the skin caused by external environmental thermal radiation (such as infrared rays in the sun), providing a continuous cooling effect for the skin, alleviating the skin's heat stress response in a high temperature environment, and reducing skin problems caused by heat damage. Furthermore, sodium alginate, calcium lactate and cellulose nanocrystals can form a stable cross-linked network, which can effectively prevent the agglomeration of cellulose nanocrystals, ensure that they are evenly dispersed in the product matrix, and enhance the stability of the product; in addition, the cross-linked network can store water and moisturize, and can evaporate and cool down while radiating cooling, achieving multiple cooling effects, and further improving the skin's tolerance in a high temperature environment. At the same time, sodium alginate and cellulose are both materials of natural origin, and calcium lactate is also a relatively safe compound. Using them to modify cellulose nanocrystals and applying them in skin care products or cosmetics is in line with the current consumer trend of pursuing natural, green and safe cosmetic ingredients, and lays a good foundation for the promotion of products in the market.
[0009] In a second aspect, the present invention provides a method for preparing the modified cellulose nanocrystals, comprising the following steps:
[0010] S1, mixing the cellulose nanocrystal aqueous solution and the sodium alginate aqueous solution uniformly to obtain a mixed solution;
[0011] S2, adding calcium lactate aqueous solution to the mixed solution, stirring for reaction, and obtaining modified cellulose nanocrystals.
[0012] The method for preparing the modified cellulose nanocrystal provided by the invention is simple to operate, does not require special equipment, and is suitable for large-scale production and application.
[0013] Furthermore, the solid content of the cellulose nanocrystal aqueous solution is 1% to 4%.
[0014] Furthermore, the solid content of the sodium alginate aqueous solution is 1% to 10%.
[0015] Furthermore, the volume ratio of the cellulose nanocrystal aqueous solution to the sodium alginate aqueous solution is 1:(1-10).
[0016] Furthermore, the solid content of the calcium lactate aqueous solution is 4% to 6%.
[0017] Furthermore, the volume ratio of the calcium lactate aqueous solution to the sodium alginate aqueous solution is (0.1-1):1.
[0018] Furthermore, the stirring reaction temperature is 20° C. to 40° C., and the stirring reaction time is 10 min to 30 min.
[0019] In the modified cellulose nanocrystals prepared by the present invention, sodium alginate, calcium lactate and cellulose nanocrystals can form a cross-linked network. When added to skin care products or cosmetic emulsions, the emulsions can have a porous structure. According to the Mie scattering principle, the reflectivity in the solar light band can be enhanced, and the absorption of solar radiation heat can be reduced. At the same time, the CO and COC bonds in the cross-linked network are at 770-1250cm -1 A strong infrared stretching vibration absorption peak can be generated within the range, which is just at the position of the atmospheric transparent window. Therefore, the modified cellulose nanocrystals have high absorption characteristics in the mid-infrared band, so that they have strong infrared reflectivity in the atmospheric window, realizing radiation cooling and cooling. At the same time, the modified cellulose nanocrystals also have a moisturizing function, which is beneficial to maintaining the moisture of the skin, allowing users to enjoy the coolness and comfort brought by radiation cooling while getting a pleasant use experience, thereby improving the competitiveness of the product in the market.
[0020] Furthermore, the method for preparing cellulose nanocrystals comprises the following steps:
[0021] Add microcrystalline cellulose to the acid solution, stir and hydrolyze for 1h to 5h, add water to terminate the reaction, let it stand, discard the supernatant, centrifuge the remaining suspension, and dialyze the obtained suspension to a pH of 6 to 7 to obtain cellulose nanocrystals.
[0022] As a specific embodiment of the present invention, the method for preparing cellulose nanocrystals specifically comprises the following steps:
[0023] A sulfuric acid solution with a mass concentration of 25% to 65% is added to a flask, and microcrystalline cellulose is added in a ratio of the mass ratio of sulfuric acid solution to microcrystalline cellulose (1 to 20): 1, and the mixture is fully stirred for hydrolysis for 1 h to 5 h. Then, deionized water in an amount 8 to 12 times the volume of the sulfuric acid solution is immediately added to terminate the reaction. After fully stirring, the mixture is allowed to stand for 8 h to 12 h, and the supernatant is poured out. The remaining suspension is centrifuged and washed, and then the supernatant is poured out, and deionized water is added to wash the precipitate. Centrifugation is continued until no stratification occurs. The obtained suspension is poured into a dialysis bag and sealed for dialysis (molecular weight cutoff is 3500 Da) for 2 to 5 days until the pH of the suspension and its external solution is 6 to 7. After filtering and centrifuging the dialyzed suspension to remove impurities, the dialyzed suspension is filtered with a microporous filter membrane to obtain cellulose nanocrystals.
[0024] Furthermore, the particle size of the microcrystalline cellulose is 1 μm to 100 μm.
[0025] In a third aspect, the present invention also provides the use of the modified cellulose nanocrystals in the preparation of radiation cooling cosmetics or skin care products.
[0026] In a fourth aspect, the present invention provides a radiation cooling cosmetic or skin care product, including the modified cellulose nanocrystals.
[0027] As a specific embodiment of the present invention, the emulsion matrix of the skin care product or cosmetic includes: 40g-60g of vaseline, 40g-60g of glycerin, 1g-10g of hyaluronic acid, 0.1mL-3mL of vitamin E, and 0.1g-2g of squalane.
[0028] The mass ratio of the modified cellulose nanocrystal to the emulsion matrix is 1:(10-100).
[0029] The modified cellulose nanocrystals provided by the present invention are applied to radiation cooling skin care products or cosmetics, which have obvious advantages: in terms of cooling, they can effectively improve the reflectivity of cosmetics or skin care products in the sunlight band, efficiently dissipate heat, reduce skin heat stress, and protect against thermal damage; in terms of stability, the network cross-linked structure constructed by sodium alginate, calcium lactate and cellulose nanocrystals can effectively prevent the precipitation of ingredients and enhance the stability of the product; in terms of moisturizing, the cross-linked mesh structure can store water and moisturize, while maintaining the moisture of the skin, it can also cool down by evaporating water, achieving multiple cooling effects; in terms of safety, the modified cellulose nanocrystals have good compatibility with the skin, no obvious irritation and sensitization, and are suitable for all kinds of skin. The modified nanocellulose provided by the present invention can significantly improve the market competitiveness of radiation cooling skin care products or cosmetics, and open up broad prospects for the development of radiation cooling skin care products or cosmetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1The SEM images of the emulsion matrix and the radiation cooling emulsion prepared in Example 1, wherein (a) the emulsion matrix, (b) the radiation cooling emulsion;
[0031] Figure 2 Schematic diagram of a device for testing the cooling effect of a radiation cooling emulsion in an embodiment of the present invention;
[0032] Figure 3 This is a picture of the present invention testing the cooling effect of the radiation cooling emulsion in a real environment;
[0033] Figure 4 This is a diagram showing the cooling effect of the radiation refrigeration emulsion prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] In order to better illustrate the present invention, further examples are given below.
[0036] The particle size of the microcrystalline cellulose used in the following examples and comparative examples is 1 μm to 100 μm.
[0037] Example 1
[0038] The present invention provides a method for preparing modified cellulose nanocrystals, which specifically comprises the following steps:
[0039] A sulfuric acid solution with a mass concentration of 64% was prepared, and microcrystalline cellulose was added to a round-bottom flask in a ratio of 10:1 between the mass ratio of sulfuric acid solution and microcrystalline cellulose. The mixture was fully stirred for hydrolysis for 1 hour, and then deionized water in an amount 10 times the volume of the sulfuric acid solution was immediately added to terminate the reaction. After fully stirring, the mixture was allowed to stand for 10 hours, and the supernatant was discarded. The remaining suspension was centrifuged and washed at 8000 r / min. The supernatant was then discarded, and deionized water was added to wash the precipitate. Centrifugation was continued until no stratification occurred. The obtained suspension was poured into a dialysis bag and sealed for dialysis (molecular weight cutoff was 3500 Da). The water was changed 2 to 3 times in the middle, and the dialysis was performed for 2 to 5 days until the pH of the suspension and its external solution was 6 to 7. The dialyzed suspension was filtered and centrifuged to remove impurities, and then filtered with a microporous filter membrane to obtain a cellulose nanocrystal solution. The cellulose nanocrystal solution was ultrasonicated at a power of 400 W for 20 minutes and then placed in a 4° C. refrigerator for standby use.
[0040] Add 30 mL of 80°C distilled water to 1 g of sodium alginate and stir for 40 min to obtain a sodium alginate solution; add 10 mL of the prepared cellulose nanocrystal solution (solid content 1% to 4%) to the above sodium alginate solution, stir at room temperature for 2 h, then add 5 mL of calcium lactate aqueous solution (solid content 4-6%), and continue stirring at room temperature for 20 min to obtain a modified cellulose solution.
[0041] The method for preparing the radiation refrigeration emulsion using the modified fiber solution specifically comprises the following steps:
[0042] Preparation of emulsion base: Mix 50 g of vaseline, 50 g of glycerin, 5 g of hyaluronic acid, 0.5 mL of vitamin E, and 0.5 g of squalane, and emulsify for 3 h to obtain an emulsion base;
[0043] Preparation of radiation refrigeration emulsion: adding the modified cellulose nanocrystal solution prepared above into the emulsion matrix at a mass ratio of 1:20 (based on pure modified cellulose nanocrystal), emulsifying for 2 hours, and obtaining radiation refrigeration emulsion.
[0044] The SEM images of the emulsion matrix and the radiation cooling emulsion in this embodiment are as follows: Figure 1 As shown in Figure (b), it can be clearly seen that the radiation cooling emulsion contains a large number of pores, which is conducive to the efficient emission of sunlight.
[0045] The radiation cooling emulsion prepared in this example is used Figure 2 The cooling effect of the device shown was tested. The test time was in the hot summer, between 11:30 and 13:30, and the location was Langfang, China (116°340′21″E, 39°31′36″N). Figure 3 The device constructed (refer to the literature Nat. Sustain. 2023, 6 (11), 1446-1454) collects detailed temperature recording information. A K-type thermocouple is placed between the simulated skin and the lotion sample to record the temperature in real time. In order to simulate the heat generated by human metabolism, a constant input of 140 W / cm from a DC power supply is used. 2 For comparison, the cooling effects of bare simulated skin (flexible and uncovered silicone heater), simulated skin coated with emulsion matrix, and simulated skin coated with radiant cooling emulsion (application thickness of 100 μm to 1 mm) were studied. Figure 4 All parameters were calibrated to ensure that the different cooling effects were only caused by the use of different coating emulsions.
[0046] from Figure 4 It can be seen that during the period from 11:30 to 13:30, the solar radiation power (orange) is basically greater than 700W / m 2From the temperature curves of bare skin (blue), emulsion matrix (black), radiation cooling emulsion (red) and environment (gray), it can be clearly seen that the radiation cooling emulsion has a good cooling effect, cooling the temperature by 2 to 3°C on average compared with the emulsion matrix.
[0047] Example 2
[0048] The present invention provides a method for preparing modified cellulose nanocrystals, which specifically comprises the following steps:
[0049] A sulfuric acid solution with a mass concentration of 25% was prepared, and microcrystalline cellulose was added to a round-bottom flask at a mass ratio of 20:1 between the sulfuric acid solution and microcrystalline cellulose. The solution was fully stirred and hydrolyzed for 5 hours, and then deionized water in an amount 8 times the volume of the sulfuric acid solution was immediately added to terminate the reaction. The solution was fully stirred and allowed to stand for 8 hours, and the supernatant was discarded. The remaining suspension was centrifuged and washed at 10,000 r / min. The supernatant was then discarded, and deionized water was added to wash the precipitate. Centrifugation was continued until no stratification occurred. The obtained suspension was poured into a dialysis bag and sealed for dialysis (molecular weight cutoff of 3,500 Da). The water was changed 2 to 3 times in the middle, and the dialysis was performed for 2 to 5 days until the pH of the suspension and its external solution was 6 to 7. The dialyzed suspension was filtered and centrifuged to remove impurities, and then filtered with a microporous filter membrane to obtain a cellulose nanocrystal solution. The solution was ultrasonicated at a power of 400 W for 5 minutes and then placed in a 4° C. refrigerator for standby use.
[0050] Add 10 mL of 100°C distilled water to 1 g of sodium alginate and stir for 100 min to obtain a sodium alginate solution; add 10 mL of the prepared cellulose nanocrystal solution (solid content 1% to 4%) to the sodium alginate solution, stir at room temperature for 5 h, then add 10 mL of calcium lactate solution (solid content 4-6%), and continue stirring at room temperature for 10 min to obtain a modified cellulose solution.
[0051] The method for preparing the radiation refrigeration emulsion using the modified fiber solution specifically comprises the following steps:
[0052] Preparation of emulsion base: Mix 40 g of vaseline, 60 g of glycerin, 1 g of hyaluronic acid, 3 mL of vitamin E, and 2 g of squalane, and emulsify for 0.5 h to obtain an emulsion base;
[0053] Preparation of radiation refrigeration emulsion: adding the modified cellulose nanocrystal solution prepared above into the emulsion matrix at a mass ratio of 1:10 (based on pure modified cellulose nanocrystal), emulsifying for 5 hours, and obtaining radiation refrigeration emulsion.
[0054] The radiation cooling emulsion prepared above was tested according to the method of Example 1, and the temperature was reduced by 2 to 3° C. on average compared with the emulsion base.
[0055] Example 3
[0056] The present invention provides a method for preparing modified cellulose nanocrystals, which specifically comprises the following steps:
[0057] A sulfuric acid solution with a mass concentration of 55% was prepared, and microcrystalline cellulose was added to a round-bottom flask in a ratio of 1:1 between the mass ratio of sulfuric acid solution and microcrystalline cellulose. The mixture was fully stirred and hydrolyzed for 2 hours, and then deionized water in an amount 12 times the volume of the sulfuric acid solution was immediately added to terminate the reaction. After fully stirring, the mixture was allowed to stand for 12 hours, and the supernatant was discarded. The remaining suspension was centrifuged and washed at 5000 r / min. The supernatant was then discarded, and deionized water was added to wash the precipitate. Centrifugation was continued until no stratification occurred. The obtained suspension was poured into a dialysis bag and sealed for dialysis (molecular weight cutoff was 3500 Da). The water was changed 2 to 3 times in the middle, and the dialysis was performed for 2 to 5 days until the pH of the suspension and its external solution was 6 to 7. The dialyzed suspension was filtered and centrifuged to remove impurities, and then filtered with a microporous filter membrane to obtain a cellulose nanocrystal solution. The cellulose nanocrystal solution was ultrasonicated at a power of 400 W for 30 minutes and then placed in a 4° C. refrigerator for standby use.
[0058] Add 100 mL of 60°C distilled water to 1 g of sodium alginate and stir for 10 min to obtain a sodium alginate solution; add 10 mL of the prepared cellulose nanocrystal solution (solid content 1% to 4%) to the sodium alginate solution, stir at room temperature for 1 h, then add 10 mL of calcium lactate solution (solid content 4-6%), and continue stirring at room temperature for 30 min to obtain a modified cellulose solution.
[0059] The method for preparing a radiation refrigeration emulsion using the modified fiber solution specifically comprises the following steps:
[0060] Preparation of emulsion matrix: 60 g of vaseline, 40 g of glycerin, 10 g of hyaluronic acid, 0.1 mL of vitamin E, and 0.1 g of squalane were mixed and emulsified for 5 h to obtain an emulsion matrix;
[0061] Preparation of radiation refrigeration emulsion: adding the modified cellulose nanocrystal solution prepared above into the emulsion matrix at a mass ratio of 1:100 (based on pure modified cellulose nanocrystal), emulsifying for 0.5 h, and obtaining radiation refrigeration emulsion.
[0062] The radiation cooling emulsion prepared above was tested according to the method of Example 1, and the temperature was reduced by 2 to 3° C. on average compared with the emulsion base.
[0063] Comparative Example 1
[0064] This comparative example provides a radiation cooling emulsion, which is different from Example 1 only in that the modified cellulose-like nanocrystals are replaced with an equal amount of unmodified cellulose nanocrystals, and specifically comprises the following steps:
[0065] A sulfuric acid solution with a mass concentration of 64% was prepared, and microcrystalline cellulose was added to a round-bottom flask in a ratio of 10:1 between the mass ratio of sulfuric acid solution and microcrystalline cellulose. The mixture was fully stirred for hydrolysis for 1 hour, and then deionized water in an amount 10 times the volume of the sulfuric acid solution was immediately added to terminate the reaction. After fully stirring, the mixture was allowed to stand for 10 hours, and the supernatant was discarded. The remaining suspension was centrifuged and washed at 8000 r / min. The supernatant was then discarded, and deionized water was added to wash the precipitate. Centrifugation was continued until no stratification occurred. The obtained suspension was poured into a dialysis bag and sealed for dialysis (molecular weight cutoff was 3500 Da). The water was changed 2 to 3 times in the middle, and the dialysis was performed for 2 to 5 days until the pH of the suspension and its external solution was 6 to 7. The dialyzed suspension was filtered and centrifuged to remove impurities, and then filtered with a microporous filter membrane to obtain a cellulose nanocrystal solution. The cellulose nanocrystal solution was ultrasonicated at a power of 400 W for 20 minutes and then placed in a 4° C. refrigerator for standby use.
[0066] Preparation of emulsion base: Mix 50 g of vaseline, 50 g of glycerin, 5 g of hyaluronic acid, 0.5 mL of vitamin E, and 0.5 g of squalane, and emulsify for 3 h to obtain an emulsion base;
[0067] Preparation of radiation refrigeration emulsion: adding the above prepared cellulose nanocrystal solution to the emulsion matrix at a mass ratio of 1:20 (based on pure cellulose nanocrystals), emulsifying for 2 hours, and obtaining radiation refrigeration emulsion.
[0068] The radiation cooling emulsion prepared above was tested according to the method of Example 1, and the temperature was reduced by 0.4-0.8° C. on average compared with the emulsion base.
[0069] In summary, the radiation cooling emulsion prepared in the embodiment of the present invention can be applied to the field of skin care products or cosmetics (such as sunscreen lotion in summer), and can achieve a temperature reduction of 2 to 3°C, achieving the dual effects of preventing sunburn and keeping the skin cool. The materials used have good biocompatibility, are inexpensive and easily available, safe and environmentally friendly, and are easy to prepare on a large scale. It has important application prospects in the field of human thermal management and energy conservation in high temperature weather in summer.
[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A modified cellulose nanocrystal, characterized in that: It is prepared by modifying cellulose nanocrystals with sodium alginate and calcium lactate.
2. The method for preparing modified cellulose nanocrystals according to claim 1, characterized in that: The steps include: S1, mixing the cellulose nanocrystal aqueous solution and the sodium alginate aqueous solution uniformly to obtain a mixed solution; S2, adding calcium lactate aqueous solution to the mixed solution, stirring for reaction, and obtaining modified cellulose nanocrystals.
3. The method for preparing modified cellulose nanocrystals according to claim 2, characterized in that: The solid content of the cellulose nanocrystal aqueous solution is 1% to 4%; and / or The solid content of the sodium alginate aqueous solution is 1% to 10%.
4. The method for preparing modified cellulose nanocrystals according to claim 3, characterized in that: The volume ratio of the cellulose nanocrystal aqueous solution to the sodium alginate aqueous solution is 1:(1-10).
5. The method for preparing modified cellulose nanocrystals according to claim 2, characterized in that: The solid content of the calcium lactate aqueous solution is 4% to 6%.
6. The method for preparing modified cellulose nanocrystals according to claim 5, characterized in that: The volume ratio of the calcium lactate aqueous solution to the sodium alginate aqueous solution is (0.1-1):
1.
7. The method for preparing modified cellulose nanocrystals according to claim 2, characterized in that: The stirring reaction temperature is 20° C. to 40° C., and the stirring reaction time is 10 min to 30 min.
8. The method for preparing modified cellulose nanocrystals according to claim 2, characterized in that: The preparation method of the cellulose nanocrystals comprises the following steps: Add microcrystalline cellulose to the acid solution, stir and hydrolyze for 1h to 5h, add water to terminate the reaction, let it stand, discard the supernatant, centrifuge the remaining suspension, and dialyze the obtained suspension to a pH of 6 to 7 to obtain cellulose nanocrystals.
9. Use of the modified cellulose nanocrystals according to claim 1 in preparing radiation cooling cosmetics or skin care products.
10. A radiation cooling cosmetic or skin care product, characterized in that: Comprising the modified cellulose nanocrystals as described in claim 1.